2021
DOI: 10.1155/2021/4884537
|View full text |Cite
|
Sign up to set email alerts
|

Salivary and Serum Interleukin-10, C-Reactive Protein, Mean Platelet Volume, and CRP/MPV Ratio in the Diagnosis of Late-Onset Neonatal Sepsis in Full-Term Neonates

Abstract: Salivary markers could serve as potential noninvasive markers in the diagnosis of neonatal infections. We aimed to investigate the diagnostic role of salivary and serum interleukin 10 (IL-10), C-reactive protein (CRP), mean platelet volume (MPV), and CRP/MPV ratio in the diagnosis of late-onset neonatal sepsis in full-term neonates. Seventy full-term neonates were enrolled in this prospective case-control study, 35 with late-onset neonatal sepsis, and 35 controls. Salivary IL-10, serum IL-10, and CRP concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
2
7
1
Order By: Relevance
“…In contrast, IL-10 seems very interesting since it could have avoided unjusti ed antibiotics for two-thirds of patients. This is consistent with that reported in a previous study exploring the performance of IL-10 for the diagnosis of LOS in in a population of fullterm neonates; 25 and the reason is likely to be related to the immune response during neonatal period, notably in preterm infants, being polarized towards an anti-in ammatory response (T helper 2 lymphocytes), involving an increased production of cytokines such as IL-10. 26 In addition, NGAL is another biomarker that had good performance to identify not infected neonates herein.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, IL-10 seems very interesting since it could have avoided unjusti ed antibiotics for two-thirds of patients. This is consistent with that reported in a previous study exploring the performance of IL-10 for the diagnosis of LOS in in a population of fullterm neonates; 25 and the reason is likely to be related to the immune response during neonatal period, notably in preterm infants, being polarized towards an anti-in ammatory response (T helper 2 lymphocytes), involving an increased production of cytokines such as IL-10. 26 In addition, NGAL is another biomarker that had good performance to identify not infected neonates herein.…”
Section: Discussionsupporting
confidence: 92%
“…This innovative approach explains why the threshold value for the biomarkers of the present study differed from the ones reported elsewhere; for example the cut-off for IL-10 in our study was 2.5 to 4.5-fold lower than the ones proposed in previous studies. 25,31 Another point of note is that the study of 11 biomarkers was possible by the use of ELLA Automated Immunoassay System that requires only 25 µL of serum for the quanti cation of 4 proteins, 32 such a low volume of blood being a prerequisite in the speci c population of neonates and very low birth weight infants to avoid blood depletion. To the best of our knowledge this is the rst time this method was used in neonates and this opens new prospects for future research, but this technique is not able to be applied to clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of technology, there is a growing interest in the use of noninvasive techniques, such as salivary assays, for monitoring, diagnosis, and prognosis, especially in vulnerable populations such as neonates (Shakeeb et al, 2021; Yen et al, 2021). From a scientific research perspective, several studies demonstrated the relationship between body fluids and the pathophysiology of various adverse clinical conditions (Min et al, 2023; Omran, Sobh et al, 2021; Sun et al, 2019; Wang et al, 2021). In terms of care, the use of biomarkers as diagnostic/prognostic tools has led to significant advances in the appropriate and individualized treatment of a range of systemic conditions, metabolic diseases, cognitive functions, stress assessment, and evaluation of immune and inflammatory responses (da Silveira Cruz-Machado et al, 2021; Min et al, 2023; Pappa et al, 2019; Pinato et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Positive correlation has already been demonstrated between salivary and plasma levels of IL-10 and C-reactive protein (CRP) in septic neonates (Omran, Sobh et al, 2021), comparison of salivary cytokine concentrations (IL-1β, IL-4, IL-7, IL-8, and TNFα) in healthy children and those with burns (Carlton et al, 2022), and correlations between salivary levels of CRP, IL-2, and interferon (IFN)-γ with serum levels in adolescents (Byrne et al, 2013). In addition, there is a correlation between salivary and plasma cytokines in healthy adults (Hanneman et al, 2016; Nam et al, 2019; Williamson et al, 2012) and in adolescents (Riis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%